Tardive Dyskinesia: A Complicated Iatrogenic Movement Condition-An Updated Overview of Diagnosis, Management, and Pharmacological Treatment - ALSHAMMARI, Sheddi RAFFAA HAMAD; Almutairi, Yousef Tala Taye; Alotaibi, Sultan Jahaz F; Aldosari, Abdullah Mubarak M; ABUDALLI, ABDULRHMAN NASSER S; Alfraidi, Abdullah Marzouq; Nammazi, Fatimah Abdulrahman; Aldosary, Salem Mazhor Khalaf; ALAMRI, SAAD DHAIFALLAH; ALDOSSARY, MISHAL FAHAD; Alshehri, Sultan SAAD (Journal of Ecohumanism, 2024)
Background: Tardive dyskinesia (TD) is a complex iatrogenic movement disorder resulting from prolonged dopamine receptor antagonism. It presents as involuntary abnormal movements such as akathisia, dystonia, and buccolingual stereotypy, predominantly affecting individuals on long-term antipsychotics. Despite the cessation of the causative medication, symptoms often persist, complicating management. Aim: This review provides an updated overview of the diagnosis, management, and pharmacological treatment options for TD, emphasizing its multifaceted nature and the challenges it presents. Methods: The article synthesizes current evidence on TD's etiology, pathophysiology, clinical presentation, and treatment strategies. Key diagnostic tools, including the Abnormal Involuntary Movement Scale (AIMS), and therapeutic approaches such as vesicular monoamine transporter (VMAT2) inhibitors, are discussed. Results: The etiology of TD is linked to first- and second-generation antipsychotics, with the former posing a greater risk. Pathophysiological insights highlight dopamine receptor hypersensitivity, oxidative stress, and neurotransmitter interactions as pivotal contributors. Diagnosis is reliant on symptom persistence post-medication exposure. While treatment options remain limited, valbenazine and deutetrabenazine show efficacy. Preventative measures, including cautious prescribing and regular monitoring, are crucial. Conclusion: TD remains a challenging condition with significant implications for affected individuals. Comprehensive evaluation and targeted therapies are essential for effective management. Advances in VMAT2 inhibitors offer promise, but prevention through judicious medication use is paramount.